Estimates of Domestic Resource Cost in Philippines Agriculture - Briones, Roehlano M. (World Bank, Washington, DC, 2014)
This study is part of a World Bank review of major issues in agribusiness in the Philippines that aims at (i) strengthening the analytical underpinnings of the current and future portfolio of operations of the Bank in the Agriculture and Rural Development (ARD) sector of the Philippines, consolidating analytical work carried out in the past two to three years and provide critical inputs for project design; and (ii) building capacities and developing a common understanding and platform with counterparts on how the results of this analysis could inform future policies and programs in the agriculture and agribusiness sector of the Philippines. The study updates the last round of domestic resource cost (DRC) estimations done by Gergely (2010), and continues work done on agricultural policy indicators for the Philippines. The rest of this report is organized as follows: the methodology for DRC analysis is presented in Section 2. A review of commodity profiles and past estimates is provided in Section 3. Section 4 presents the results and analysis of applying the DRC method. Section 5 summarizes and makes recommendations.